Dediščina z območja občin Brežice in Krško kot osnova za razvoj temačnega turizma - Kužnik, Lea (Etnolog. Nova vrsta (Ljubljana), 2017)
Dark tourism is a special type of tourism that started to develop in the 20th century and involves visiting sights and destinations associated with death, suffering, accidents, and the locations of tragedies. The article presents the concept and typology of dark tourism, to then identify the heritage from the area of the municipalities of Brežice and Krško with potential for inclusion in dark tourism. The authors conclude that the area of the two municipalities features heritage connected with cemeteries, castles, paranormal phenomena, witchcraft processes, peasant uprisings, and the Second World War, which could be included in the tourist assets of both municipalities in the framework of dark tourism.
Keywords: ethnology; etnologija; ljudska verovanja; temačni turizem; pokopališča; gradovi; Brežice; Krško